Social Support Moderates the Relationship Between Perceived Stress and Quality of Life in Patients With a Left Ventricular Assist Device. Issue 5 (September 2018) - Abshire, Martha; Russell, Stuart D.; Davidson, Patricia M.; Budhathoki, Chakra; Han, Hae-Ra; Grady, Kathleen L.; Desai, Shashank; Dennison Himmelfarb, Cheryl
Abstract : Background: Living with a left ventricular assist device has significant psychosocial sequelae that affect health-related quality of life (HRQOL). Objective: The purpose of this study was to (1) describe psychosocial indicators of stress including perceived stress, depression, fatigue, and coping; (2) examine relationships among stress indicators by level of perceived stress; (3) examine relationships among indicators of stress and clinical outcomes; and (4) test the moderation of social support on the relationship between stress and clinical outcomes. Methods: Participants were recruited from 2 outpatient clinics in a cross-sectional study design. Standardized measures were self-administered via survey. Descriptive statistics, correlation, and multiple linear regression analysis were conducted. Results: The sample (N = 62) was mostly male (78%), black (47%), and married (66%), with a mean age of 56.5 ± 13 years. The overall sample had a moderate stress profile: moderate perceived stress (mean, 11.7 ± 7), few depressive symptoms (mean, 3.2 ± 3.9), and moderate fatigue (mean, 14.3 ± 9.1). Increased perceived stress was associated with fatigue, depressive symptoms, and maladaptive coping ( P < .001). Regression analysis demonstrated that perceived stress and fatigue were significant correlates of overall HRQOL (adj. R 2 = 0.41, P < .0001). Social support moderated the relationship between perceived stress and HRQOL, controlling for fatigue ( R 2 = 0.49, P < .001). Conclusions: Individuals living with left ventricular assist device with high perceived stress have worse depressive symptoms, fatigue, and coping. The influence of high social support to improve the relationship between stress and HRQOL underscores the importance of a comprehensive plan to address psychosocial factors.